TEACHING ENGLISH GRAMMAR WITH CLT AND EXPLANATION METHOD - Haryanto, Subaidi (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2015)
Teaching English grammar can be taught by some methods. Two of them are communicative language teaching (CLT) and explanation method. Both CLT and explanation method can be used to present the English language materials such as authentic materials, Scrambled sentences, language games, picture strip stories, poems, songs, poetry, map, and role play. Each of them has strength and weakness. Teaching with CLT can make the class become interesting and the student will not get bored. Whereas, by only using the explanation the student will get bored and the teacher as well. In Indonesia CLT is a modified version to adopt teaching English skills such as reading, writing and and speaking. Structural approach is still applied for teaching language elements such as structure/grammar and vocabulary. Explanation method is used to develop reading skill. However, based on the data of test result by the students, the result of explanation technique is more effectively targeted better than CLT.Â Keywords: grammar, communicative, explanation, technique, teaching